Terror in the dirt: Sensory determinants of host seeking in soil-transmitted mammalian-parasitic nematodes - Bryant, Astra S. (Int J Parasitol Drugs Drug Resist, 2018)
Infection with gastrointestinal parasitic nematodes is a major cause of chronic morbidity and economic burden around the world, particularly in low-resource settings. Some parasitic nematode species, including the human-parasitic threadworm Strongyloides stercoralis and human-parasitic hookworms in the genera Ancylostoma and Necator, feature a soil-dwelling infective larval stage that seeks out hosts for infection using a variety of host-emitted sensory cues. Here, we review our current understanding of the behavioral responses of soil-dwelling infective larvae to host-emitted sensory cues, and the molecular and cellular mechanisms that mediate these responses. We also discuss the development of methods for transgenesis and CRISPR/Cas9-mediated targeted mutagenesis in Strongyloides stercoralis and the closely related rat parasite Strongyloides ratti. These methods have established S. stercoralis and S. ratti as genetic model systems for gastrointestinal parasitic nematodes and are enabling more detailed investigations into the neural mechanisms that underlie the sensory-driven behaviors of this medically and economically important class of parasites.